2022
DOI: 10.1111/cod.14245
|View full text |Cite
|
Sign up to set email alerts
|

Topical eye medications causing allergic contact dermatitis

Abstract: Background: Allergic contact dermatitis (ACD) in the eye region caused by topical eye medications is difficult to diagnose and may be overlooked.Objective: To study the characteristics and causative agents in patients with ACD caused by topical eye medications in a Danish tertiary dermatology department.Methods: A retrospective study of 318 patients, patch tested between 2013 and 2021 due to suspected ACD to topical eye medications. All patients were tested with a locally developed eye medication series, some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
16
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(29 citation statements)
references
References 22 publications
10
16
3
Order By: Relevance
“…4,6 Ahlström et al further showed a negative association between the presence of atopic dermatitis and positive patch test reactions to TOMs. 7 In concordance with these findings, none of the patients with ACD from TOMs in our study exhibited atopic features.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…4,6 Ahlström et al further showed a negative association between the presence of atopic dermatitis and positive patch test reactions to TOMs. 7 In concordance with these findings, none of the patients with ACD from TOMs in our study exhibited atopic features.…”
Section: Discussionsupporting
confidence: 90%
“…present series (0.9%). Among those patch tested due to suspected TOM-induced periorbital ACD, the share of sensitization has been reported as 12.9%-67.7% in previous studies, 6,7,18 while this rate was 33.3% in our study.…”
Section: Discussioncontrasting
confidence: 44%
See 3 more Smart Citations